Teaching Process Mineralogy in Australia - Quinton, Stephen; Vaughan, Jeff; Davidson, L.; Nemchin, Alexander (The National Association of Geoscience Teachers, 2004)
The increasing complexity of ores processed today necessitates more detailed mineralogical characterisation than in the past. To ensure that metallurgists have the skills and knowledge required for this the Minerals Council of Australia is funding the preparation of curriculum materials for use in undergraduate and postgraduate courses in process mineralogy. Each course represents 75 contact hours of instruction and is being introduced progressively at universities in the Minerals Council's Australian network. Their modular format and appropriate use of WWWtechnologies mean the courses can be delivered to external students as well as those on campus. The undergraduate course adopts an active learning strategy with tasks written to "wrap around" established textbooks. Emphasis is on characterisation of ore minerals and mill products. All students will develop basic skills in reflected light microscopy using a virtual polarising microscope tutorial being prepared as a CD ROM. The postgraduate course develops understanding of sophisticated analytical techniques and their application: image analysis, advanced beam techniques for chemical analysis (including proton microprobe, dynamic SIMS, ICP-MS) and surface analysis. Case study material provides opportunities for students in both courses to study the application of mineralogy to problems in mineral processing and extractive metallurgy.